Effect of coumarin backbone in N^O type nickel catalyzed olefin polymerization. (17th February 2023) - Qasim, Muhammad; Tian, Wanlu; Pang, Wenmin; Pan, Yao; Behzadi, Shabnam; Chen, Min
Graphical abstract: Easily available biomass coumarin based nickel catalysts for ethylene, norbornene homo-polymerization and copolymerization. Highlights: First time, exploration of Biomass coumarin based novel backbone in N^O type neutral nickel catalysts. The laconic part being in conjugation with metal center may generate the zwitterionic conditions. Catalysts were used in ethylene polymerization, norbornene polymerization and copolymerization. Sterically less hindered catalyst Ni1 provided the higher incorporation ratios of 5-norbornene-2-carboxylic methyl ester up to 22.2 mol% and 5-norbornene-2-methanol up to 28.9 mol%. Abstract: Designing and synthesis of easily available nickel based catalysts has become an attractive research direction in olefin polymerization. In this contribution, novel coumarin-type N^O nickel catalysts with sterically and electronically varied substituents were synthesized and applied in ethylene polymerization, norbornene homopolymerization and copolymerization. Sterically hindered catalysts Ni2 -Ni4 behaved in good performance, generating polyethylene with higher molecular weight. On the other hand, for the norbornene copolymerization process, sterically less hindered Ni1 mediated the higher incorporation ratios both for 5-norbornene-2-carboxylic methyl ester up to 22.2 mol% and 5-norbornene-2-methanol up to 28.9 mol%. The simple synthesis and the possibility of tuning their catalytic properties with Lewis acid addition make this system highly attractive for further exploration.